Приближение плотностей абсолютно непрерывных компонент мер и гильбертовом пространстве с помощью полугруппы Орнштейна — Уленбека - Руденко, А.В. (Український математичний журнал, 2004)
Вивчається поведінка мір, які є результатом дії пігрупи Орнштейна - Улеибека Tt, що пов'язана з гауссовою мірою μ, на довільну ймовірнісну міру ν у сепарабельному гільбертовому просторі, при t→0+. Доведено, що щільності абсолютно неперервних частин Ttν по відношенню до μ збігаються за мірою |і до щільності абсолютно неперервної частини V по підношенню до μ. У випадку скінченної вимірності простору доведено збіжність цих щільпостей μ-майже скрізь. У нескіпченновимірному випадку наведено деякі достатні умови для збіжності майже скрізь. Також розглянуто умови па абсолютну неперервність Ttν по відношенню до μ. у термінах коефіцієнтів розкладу Ttν в ряд за поліномами Ерміта (аналог розкладу Іто - Вінера) та зв'язок з фінітною абсолютною неперервністю. We study the behavior of measures obtained as a result of the action of the Ornstein-Uhlenbeck semigroup T t associated with the Gaussian measure μ on an arbitrary probability measure ν in a separable Hilbert space as t → 0+. We prove that the densities of the parts of T t ν absolutely continuous with respect to μ converge in the measure μ to the density of the part of ν absolutely continuous with respect to μ. For a finite-dimensional space, we prove the convergence of these densities μ-almost everywhere. In the infinite-dimensional case, we give sufficient conditions for almost-everywhere convergence. We also consider conditions on the absolute continuity of T t ν with respect to μ in terms of the coefficients of the expansion of T t ν in a series in Hermite polynomials (an analog of the Ito- Wiener expansion) and the connection with finite absolute continuity.